Pengaruh Beban Kerja Dan Kerjasama Tim Terhadap Kinerja Pegawai Pada Kantor Badan Penanggulangan Bencana Daerah (BPBD) Kabupaten Sikka - Fransiska Nineng; Imanuel Wellem; Maria Modesta Missi Mone (Jurnal CUAN Universitas Nusa Nipa Maumere, 2025)
The Regional Disaster Management Agency of Sikka Regency is a regional implementing entity in the field of disaster management. It is led by an executive head who is answerable to the Regent of Sikka through the regional secretary. The position is an officio one. The objective of this study is twofold: firstly, to ascertain the description of employee perfomance, workload and teamwork; secondly, to analyse the effect of workload and teamwork on employee performance, both partially and simultaneously. The population under investigation in this study was constituted by the employees of the Sikka Regency Regional Disaster Management Agency, amounting to a total of 35 individuals. Given the limited size of the population, the research was conducted through census or saturated sampling. Data were collected through questionnaires and analysed using descriptive and inferential statistical methods, namely multiple linear regression. Hypothesis testing was conducted through F-test and t-test. The results of the descripyivr analysis indicate that the variables pertaining to employee perfomance, workload and teamwork are all situated within the acceptable range of criteria. The results of the t-test indicate that, to some extent, the workload variable exerts a negative and statistically significant influence on employee performance. Moreover, the teamwork variable has a positive and significant effect on employee performance. The statistical results of the F-test demonstrate that the simultaneous influence of workload and teamwork variables on employee performance is statistically significant. The results of the determination analysis indicate that the two independent variables in thstudy are capable of explaining the observed variation in the performance of the Sikka Regency Regional Disaster Management Agency employees by 23.8%.